2008
DOI: 10.1056/nejmoa0707035
|View full text |Cite
|
Sign up to set email alerts
|

D2 Lymphadenectomy Alone or with Para-aortic Nodal Dissection for Gastric Cancer

Abstract: As compared with D2 lymphadenectomy alone, treatment with D2 lymphadenectomy plus PAND does not improve the survival rate in curable gastric cancer. (ClinicalTrials.gov number, NCT00149279.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
588
7
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 917 publications
(636 citation statements)
references
References 32 publications
27
588
7
14
Order By: Relevance
“…The overall operative mortality rate of 1.6 % compares favorably with data from large contemporary audits, with the 2010 esophagogastric cancer audit of England and Welsh hospitals reporting an in-hospital mortality rate of 6 % for patients undergoing curative gastric resection [31]. The operative mortality rate of 2.5 % for our patients selected to have a D2 resection is comparable to the results published from internationally renowned centers [9,17,18,20] and is significantly less than the mortality rates reported from two of the published randomized trials of D1 versus D2 resection [11,32,33]. It is worth noting that we have performed far fewer resections involving the pancreas and the spleen, which was a major source of morbidity in the Dutch study [11].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The overall operative mortality rate of 1.6 % compares favorably with data from large contemporary audits, with the 2010 esophagogastric cancer audit of England and Welsh hospitals reporting an in-hospital mortality rate of 6 % for patients undergoing curative gastric resection [31]. The operative mortality rate of 2.5 % for our patients selected to have a D2 resection is comparable to the results published from internationally renowned centers [9,17,18,20] and is significantly less than the mortality rates reported from two of the published randomized trials of D1 versus D2 resection [11,32,33]. It is worth noting that we have performed far fewer resections involving the pancreas and the spleen, which was a major source of morbidity in the Dutch study [11].…”
Section: Discussionsupporting
confidence: 70%
“…Extended lymphadenectomy (D2/D3) for Electronic supplementary material The online version of this article (doi:10.1007/s10120-013-0240-3) contains supplementary material, which is available to authorized users. gastric cancer is routinely performed in Japanese surgical units [7,8], with large reported series demonstrating that it can be performed safely [9,10]. Two European randomized studies assessing the role of extended lymph node dissection (D2) failed to show any improvement in survival [11,12], but with associated higher mortality and morbidity rates in the extended lymphadenectomy group, as a result of splenic and pancreatic resection.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate trial, Sasako et al . was able to demonstrate the feasibility of carrying out para‐aortic dissection on top of D2 lymphadenectomy for gastric cancer, although there was no benefit to the 5‐year overall survival 24, 25. Most recently, Sano et al 26.…”
Section: Gastric Surgerymentioning
confidence: 99%
“…A recent reported clinical trial, at 24 japanese hospitals, comparing D2 lymphadenectomy alone with D2 procedure with para-aortic nodal dissection for gastric cancer, has shown that no improvement in the survival rate has been obtained 30 .…”
Section: Discussionmentioning
confidence: 99%